2005
DOI: 10.4141/s04-054
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil nitrogen supply in potato fields using a plant bioassay approach

Abstract: G. 2005. Estimation of soil nitrogen supply in potato fields using a plant bioassay approach. Can. J. Soil Sci. 85: [377][378][379][380][381][382][383][384][385][386]. Soil N supply is an important contributor of N to crop production; however, there is a lack of practical methods for routine estimation of soil N supply under field conditions. This study evaluated sampling just prior to topkill of whole potato plants that received no fertilizer N as a field bioassay of soil N supply. Three experiments were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 23 publications
0
42
1
Order By: Relevance
“…Previous studies in this region also measured generally low soil mineral N contents in spring, particularly for a preceding cereal crop (Be´langer et al 1998;Zebarth et al 2005a). Soil N supply in this study ranged from 34 to 66 kg N ha (1 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies in this region also measured generally low soil mineral N contents in spring, particularly for a preceding cereal crop (Be´langer et al 1998;Zebarth et al 2005a). Soil N supply in this study ranged from 34 to 66 kg N ha (1 .…”
Section: Discussionmentioning
confidence: 58%
“…( Above-ground plant N accumulation with no fertilizer N application was used as a measure of soil N supply (Zebarth et al 2005a). All above-ground plant tissue was harvested by hand in a 0.89-m 2 area within each plot for the 0-kg N ha…”
Section: Methodsmentioning
confidence: 99%
“…Soil mineral N content has also been shown to be useful in optimizing fertilizer N recommendations for cereal crops in humid environments (Harrison 1995;Bundy and Andraski 2004). However, in some humid regions such as Atlantic Canada, soil mineral N content is generally low in spring, and soil N supply is determined primarily by soil N mineralization (Bélanger et al 1998;Zebarth et al 2005). There is currently no practical method of predicting soil N mineralization prior to seeding a cereal crop.…”
Section: Mots Clésmentioning
confidence: 99%
“…Of course, this is possible only having a good knowledge about the local farming conditions. Similar approach is supported also by other researchers (Schepers, Meisinger, 1994;Sanderson et al, 1999;Bélanger et al, 2000;Olfs et al, 2005;Zebarth et al, 2005). Soil nitrogen supply should be taken into consideration when making fertiliser nitrogen recommendations, but there is a lack of practical methods for routine estimation (analysing) of soil nitrogen supply under field conditions.…”
Section: Introductionmentioning
confidence: 67%
“…However, some authors point out that close agreement between these experiments and field measurements is mostly lacking (Hofman et al, 1985;Sharifi et al, 2007;Ros, 2011). For example, research done with potatoes showed that nitrogen recommendations based on soil analysis were no better than those based on the information of previous cropping and soil type (Zebarth et al, 2005). Therefore the authors of the United Kingdom fertiliser recommendation guide suggest that, since research has not yet identified a preferred laboratory method that is suitable for routine use, measurement of the topsoil organic matter content and computer modelling could give more useful indications (Fertiliser Manual, 2010).…”
Section: Introductionmentioning
confidence: 99%